2010
DOI: 10.1158/1078-0432.ccr-09-1865
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of p53/MDM2/p14ARF Pathway Abnormalities in Relapsed Neuroblastoma

Abstract: Purpose: Most neuroblastomas initially respond to therapy but many relapse with chemoresistant disease. p53 mutations are rare in diagnostic neuroblastomas, but we have previously reported inactivation of the p53/MDM2/p14 ARF pathway in 9 of 17 (53%) neuroblastoma cell lines established at relapse. Hypothesis: Inactivation of the p53/MDM2/p14 ARF pathway develops during treatment and contributes to neuroblastoma relapse. Methods: Eighty-four neuroblastomas were studied from 41 patients with relapsed neuroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
152
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 42 publications
(49 reference statements)
5
152
0
1
Order By: Relevance
“…Recent studies found that, about half of the relapsed neuroblastoma tumors had aberrations in the p53/MDM2/p14 ARF pathway, with one-third being p53 mutations and two-third being MDM2/ p14 ARF abnormalities. 13 Thus, even if not all MDM2/p14 ARF abnormalities were responsive to Chk1 inhibition as our findings suggested, it is conceivable about one-third of all relapsed neuroblastoma patients could potentially benefit from a combination therapy utilizing Chk1 inhibitor and chemotherapeutic drug. Moreover, since recent studies suggest that most p53 mutations found in neuroblastomas are acquired after chemotherapy, while MDM2/p14 ARF abnormalities and MDM2 polymorphism are found primarily at diagnosis, 8,10,11,13 it seems reasonable to exploit Chk1 inhibitors either early on at diagnosis in patients with documented MDM2/p14 ARF abnormalities, or after recurrence when tumors have acquired p53 mutations.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recent studies found that, about half of the relapsed neuroblastoma tumors had aberrations in the p53/MDM2/p14 ARF pathway, with one-third being p53 mutations and two-third being MDM2/ p14 ARF abnormalities. 13 Thus, even if not all MDM2/p14 ARF abnormalities were responsive to Chk1 inhibition as our findings suggested, it is conceivable about one-third of all relapsed neuroblastoma patients could potentially benefit from a combination therapy utilizing Chk1 inhibitor and chemotherapeutic drug. Moreover, since recent studies suggest that most p53 mutations found in neuroblastomas are acquired after chemotherapy, while MDM2/p14 ARF abnormalities and MDM2 polymorphism are found primarily at diagnosis, 8,10,11,13 it seems reasonable to exploit Chk1 inhibitors either early on at diagnosis in patients with documented MDM2/p14 ARF abnormalities, or after recurrence when tumors have acquired p53 mutations.…”
Section: Discussionmentioning
confidence: 58%
“…10,11 Deregulation of the p53/MDM2/p14 ARF pathway has also been linked to TWIST1, BMI1, PPM1D, and loss of CHD5, as well as cytoplasmic sequestration of p53. 12 The high frequency ($ 50%) of aberrations in the p53/MDM2/ p14 ARF pathway found in both neuroblastoma cell lines established at relapse and in relapsed neuroblastoma tumors 7,13 raises the possibility that p53 pathway defect could be a key de novo and acquired chemoresistance mechanism. 12 In this study, we utilized a representative panel of neuroblastoma cell lines with aberrations in their p53/MDM2/ p14 ARF pathway, to study their G 1 checkpoint status and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable feature is that p53 is rarely mutated at diagnosis and only in a minority of neuroblastoma tumors at relapse, as shown by a recent study that found mutation rates of 2% and 15%, respectively (3). Conflicting data exist about p53 pathway signaling in neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a higher incidence of p53 mutations was found in a study on 84 neuroblastomas from 41 patients with relapsed disease, including 38 paired neuroblastomas at different stages of therapy. Inactivating missense p53 mutations were identified in 6/41 (15%) cases, 5 following chemotherapy and/or at relapse and only 1 at both diagnosis and relapse (Carr-Wilkinson, O'Toole et al, 2010). Studies on neuroblastoma cell lines demonstrated that loss of p53 function due to mutations of p53 gene or gene silencing by p53 shRNA can confer multidrug resistance to neuroblastoma cells (Keshelava, Zuo et al, 2000;Keshelava, Zuo et al, 2001;Xue, Haber et al, 2007).…”
Section: Targeting the P53 Pathwaymentioning
confidence: 99%
“…In the majority of neuroblastoma tumours maintaining wild-type p53 gene, an increasing amount of data shows that the p53 pathway may not be functional due to non-mutational mechanisms. For example, a high incidence of abnormalities in the p53/MDM2/p14 ARF pathway was found in human neuroblastoma cell lines established at relapse (53%) (Carr, Bell et al, 2006) and patient samples at relapse (49%) (Carr-Wilkinson, O'Toole et al, 2010). MDM2, the essential negative regulator of p53, is transcriptionally regulated by the MYCN oncogene in neuroblastoma (Slack, Chen et al, 2005).…”
Section: Targeting the P53 Pathwaymentioning
confidence: 99%